Association of epicardial fat volume with the severity of coronary artery disease: a preliminary study on risk prediction of obstructive coronary heart disease - Hangyi Zhou; Yuxin Pan; Juan Du; Fen Liang; Xiaojun Ma; Dongling Lv (BMC Cardiovascular Disorders)
Abstract Background We aimed to explore the correlation between epicardial fat volume (EFV) and the severity of coronary atherosclerotic artery disease (CAD), evaluate the predictive value of EFV for obstructive CAD, and provide prediction for the selection of clinical treatment schemes for CAD. Methods A total of 203 patients undergoing chest computed tomography (CT) and Coronary Artery Angiography (CAG) were included in this retrospective study. The severity of coronary stenosis and SYNTAX score were evaluated by CAG images. There were 141 patients in obstructive CAD group which was defined as coronary stenosis severity ≥ 70% and 62 patients in non obstructive CAD group. Results Multivariate logistic regression analysis showed that after adjusting for confounding factors, EFV (OR, 1.008; 95% CI, 1.000-1.016; p = 0.039) was an independent risk factor for obstructive CAD. Spearman correlation analysis showed a significant positive correlation between EFV and SYNTAX score, as well as the number of coronary lesions (r = 0.157, p = 0.026; r = 0.231, p = 0.002). The EFV of males was significantly higher than that of females (p < 0.001). EFV was significantly positively correlated with intrathoracic fat volume (IFV) (p < 0.001). Conclusions EFV maybe an independent risk factor for obstructive CAD. Quantitative measurement of EFV by QCT can predict the severity of CAD. EFV was significantly correlated with IFV, but not with BMI. Clinical trial number Not applicable.